Age-, sex- and disease subtype–related foetal growth differentials in childhood acute myeloid leukaemia risk: A Childhood Leukemia International Consortium analysis. (May 2020) - ,; ,; Baka, Margarita; Moschovi, Maria; Polychronopoulou, Sophia; Kourti, Maria; Hatzipantelis, Emmanuel; Pelagiadis, Iordanis; Dana, Helen; Kantzanou, Maria; Tzanoudaki, Marianna; Anastasiou, Theodora; et al.
Abstract: Aim: Evidence for an association of foetal growth with acute myeloid leukaemia (AML) is inconclusive. AML is a rare childhood cancer, relatively more frequent in girls, with distinct features in infancy. In the context of the Childhood Leukemia International Consortium (CLIC), we examined the hypothesis that the association may vary by age, sex and disease subtype using data from 22 studies and a total of 3564 AML cases. Methods: Pooled estimates by age, sex and overall for harmonised foetal growth markers in association with AML were calculated using the International Fetal and Newborn Growth Consortium for the 21st Century Project for 17 studies contributing individual-level data; meta-analyses were, thereafter, conducted with estimates provided ad hoc by five more studies because of administrative constraints. Subanalyses by AML subtype were also performed. Results: A nearly 50% increased risk was observed among large-for-gestational-age infant boys (odds ratio [OR]: 1.49, 95% confidence interval [CI]: 1.03–2.14), reduced to 34% in boys aged <2 years (OR: 1.34, 95% CI: 1.05–1.71) and 25% in boys aged 0–14 years (OR: 1.25, 95% CI: 1.06–1.46). The association of large for gestational age became stronger in boys with M0/M1subtype (OR: 1.80, 95% CI: 1.15–2.83). Large birth length for gestational age was also positively associated with AML (OR: 1.38, 95% CI: 1.00–1.92) in boys. By contrast, there were null associations in girls, as well as with respect to associations of decelerated foetal growth markers. Conclusions: Accelerated foetal growth was associated with AML, especially in infant boys and those with minimally differentiated leukaemia. Further cytogenetic research would shed light into the underlying mechanisms. Highlights: Accelerated foetal growth was associated with childhood acute myeloid leukaemia. The association was marked in large-for-gestational-age newborns. The association was stronger in infant boys and minimally differentiated leukaemia. Accelerated foetal growth age-, sex- and subtype- related differentials were showed. These associations could shed light into the biology of AML and its subtypes.